TREATMENT OF TRANSGENDER CHARACTERS IN CLASS IIA RESIDENTIAL INSTITUTIONS SUMBAWA BESAR - Ahmad Sutoyo; Umar Anwar (Polteknik Ilmu Pemasyarakatan, 2019)
This research focuses on implementation, benefits, and to find out the problems faced in the treatment of prisoners with a transgender character. In this study raised the issue of how the officers and other prisoners treat transgender inmates in Penitentiary and how they affect the health, safety, and psychological well-being of transgender inmates in the Sumbawa Besar Class IIA Penitentiary. This study uses interview and observation research methods, which describe the treatment of prisoners with a transgender character, then analyzed and concluded using a qualitative approach. Based on the analysis, it was found that the treatment of transgender inmates was considered very necessary to be carried out. Prisoners with transgender characteristics are prisoners who are unique and different from prisoners in general. Generally, prisoners with the transgender character who are spread across prisons throughout Indonesia are men whose gender is women or better known as transvestites. Prisoners with a transgender character are very vulnerable to adverse treatment by other prisoners, and can also have a negative influence on other prisoners. Special treatment of prisoners with transgender character is deemed very necessary, starting from the placement in individual blocks to specific guidance for transgender inmates. There are obstacles encountered in its implementation, including the procurement of individual blocks of prisoners with transgender character and the understanding of Correctional Officers of the problems and irregularities that will be caused by the presence of transgender inmates in prison.